PROBLEM BASED LEARNING (PBL) TOWARDS STUDENTS' CRITICAL THINKING ABILITY: LITERATURE REVIEW - Nasriati, Nasriati; Winarni, Sri; Hanum, Latifah (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Following the learning objectives of the 21st century, the learning process emphasizes mastery of teaching materials and requires direct students to solve problems. Critical thinking skills are needed for students to be able to solve problems. Problem-based learning is learning that emphasizes presenting authentic problems based on phenomena in everyday life. This literature review aims to discover the importance of applying the PBL learning model to improve students' critical thinking skills in chemistry learning. The method used in this study is a literature review beginning with finding topics to make it easier to collect data. Data were obtained by searching journals through Google Scholar and Science Direct, published for the last ten years (2012-2022) using the keywords PBL, critical thinking skills, and chemistry. Based on the literature search, 15 relevant articles have been found for further analysis. The literature review results show that applying PBL learning has strong potential to improve students' critical thinking skills in various fields of study, especially chemistry. Keywords: Chemistry, Critical Thinking, PBL